2020
DOI: 10.3390/qubs4020019
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Orientation of a Block Copolymer via an Electron-Beam Induced Polarity Switch in a Nitrophenyl Self-Assembled Monolayer or Si Etching Treatments

Abstract: Directed self-assembly (DSA) was investigated on self-assembled monolayers (SAMs) chemically modified by electron beam (EB) irradiation, which is composed of 6-(4-nitrophenoxy) hexane-1-thiol (NPHT). Irradiating a NPHT by EB could successfully induce the orientation and selective patterning of block copolymer domains. We clarified that spatially-selective lamellar orientations of polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) could be achieved by a change of an underlying SAM. The change of an underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, pattern transfer blocking can be achieved in a single photolithographic exposure without involving additional processes. This similar concept of using directly patternable orientation layers was previously demonstrated with patterns created by photolithography, 48,50,52 electron beam, 45,53 and X-ray exposures, 54 but successful DSA of silicon-containing BCPs using photopatternable surface treatments has not yet been demonstrated. pGSTs, however, require aminopropyltriethoxysilane (APTES)-treated surfaces in order to be grafted to the substrate.…”
Section: ■ Introductionmentioning
confidence: 82%
“…Furthermore, pattern transfer blocking can be achieved in a single photolithographic exposure without involving additional processes. This similar concept of using directly patternable orientation layers was previously demonstrated with patterns created by photolithography, 48,50,52 electron beam, 45,53 and X-ray exposures, 54 but successful DSA of silicon-containing BCPs using photopatternable surface treatments has not yet been demonstrated. pGSTs, however, require aminopropyltriethoxysilane (APTES)-treated surfaces in order to be grafted to the substrate.…”
Section: ■ Introductionmentioning
confidence: 82%
“…(2) In addition to polymer-based materials, there are several reports on advanced ion beam technology, such as the single event effects of heavy ion beams to semiconductor devices [5], the radiation-induced modification of lattice structures and mechanical properties of metallic materials [6], and the novel preparation of nanostructured catalysts for energy devices [7,8]. (3) In the fields of nanotechnology and microfabrication processes, it was reported that low dimensional functional organic matters were created using single charged particle-induced chemical reactions in nanospace [9] and oriented lamellae of self-assembled block copolymers were designed with a single nanoscale using EB for future lithographic materials [10]. (4) Regarding novel application of quantum beam technology, this Special Issue provides the recent progress of phase imaging using synchrotron X-rays and pulsed neutron beams [11] and ultrafast electron diffractometers with relativistic electron pulses for the investigation of ultrafast structural dynamics [12].…”
mentioning
confidence: 99%